2021
DOI: 10.21511/ppm.19(2).2021.37
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative governance in handling natural and non-natural disasters based on the perspective of public administration: Evidence from Indonesia

Abstract: Both natural and non-natural disasters greatly affect human life, including business actors. The government is urgently required to solve the emerging problems caused by the disaster. This study aims to determine collaborative governance in handling natural and non-natural disasters that affect the business actors in Palu City. This study used a quantitative approach with a series of statistical tests. The sample of this study consisted of 207 respondents who are government and the business actors in Palu City… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…This collaboration is important not only in cases of handling Covid-19 but also in cases of natural and non-natural disasters [18] which can not only be resolved by the government but also requires the participation of various parties involved [19][20][21][22]. The development of this research topic shows that Covid-19 is an interesting issue when viewed from a collaborative camera and even these writings can be a reference for alternative solutions when the Covid-19 issue at any time turns into another issue.…”
Section: Research Topic Trendmentioning
confidence: 99%
“…This collaboration is important not only in cases of handling Covid-19 but also in cases of natural and non-natural disasters [18] which can not only be resolved by the government but also requires the participation of various parties involved [19][20][21][22]. The development of this research topic shows that Covid-19 is an interesting issue when viewed from a collaborative camera and even these writings can be a reference for alternative solutions when the Covid-19 issue at any time turns into another issue.…”
Section: Research Topic Trendmentioning
confidence: 99%
“…The Covid-19 pandemic in Indonesia was exacerbated by a policy direction that arguably prioritised economic considerations over public health. The government of Indonesia, in this case, was seen as having bungled the situation, mostly due to its policy choices (Lutfi et al, 2020;Asmorowati, Schubert and Ningrum, 2021;Riadi and Erdiyansyah, 2021). Eventually, the government had to pay dearly for the denials made by public officials.…”
Section: Introductionmentioning
confidence: 98%
“…Collaboration has been fully integrated into government as a public service reform. In Indonesia, many researchers have concluded that various local governments need to collaborate with another party to achieve the desired results, such as achieving SDGs in Serang City (Nurfindarti, 2019), disaster recovery in Palu (Riadi & Erdiyansyah, 2021), or stunting eradication in Bandung City (Essa et al, 2021).…”
Section: Introductionmentioning
confidence: 99%